1997
DOI: 10.1039/a703950f
|View full text |Cite
|
Sign up to set email alerts
|

First EPR characterisation of the structures and reactivities of α- and β-boryl radicals derived from boronic esters

Abstract: The first EPR observations of carbon-centred radicals with aand b-boronic ester substitutents indicated moderate thermodynamic stabilisation for the former whereas the latter had an inclination towards b-scission.Boronic acids and esters are convenient synthetic intermediates which have been widely applied in stereocontrolled reactions. 1 Recent research has shown that a-boryl radicals, generated by addition of carbon-centred radicals to alkenyl-2 and alkynylboronic esters, 3 can take part in inter-and intra-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…In agreement with this, product analyses showed that at higher temperatures the dimer 22 , derived from 19a , lessened in importance and that the major product was 1-hexene. A mechanism involving direct β-scission of 19a to produce 1-hexene and bisalkoxyboryl radical 20 was considered (Scheme ) . However, radical 20 could not be spectroscopically detected directly, by spin trapping, or on ligation with pyridine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with this, product analyses showed that at higher temperatures the dimer 22 , derived from 19a , lessened in importance and that the major product was 1-hexene. A mechanism involving direct β-scission of 19a to produce 1-hexene and bisalkoxyboryl radical 20 was considered (Scheme ) . However, radical 20 could not be spectroscopically detected directly, by spin trapping, or on ligation with pyridine.…”
Section: Discussionmentioning
confidence: 99%
“…The objectives of the present research were to investigate the ease of formation of α- and β-boronate radicals, to ascertain their modes of reaction, to assess the stabilization of these radicals by experimental and by ab initio theoretical methods, and to examine the kinetics of hydrogen abstraction adjacent to boronate functional groups. We recently reported the first EPR spectroscopic observations of transient radicals derived from boronic esters in solution and have used this technique, integrated with product analyses, to address the above aims.…”
mentioning
confidence: 99%
“…Our long‐standing interest in developing mild methods for the functionalization of alkenes through radical pathways inspired us to investigate iodoalkylation involving 1‐borylated alkyl radicals to give γ‐iodoalkylboronates. Based on EPR studies and calculations, Walton, Carboni, and co‐workers reported that 1‐borylated radicals are stabilized when the boron is sp 2 ‐hybridized, however the extent of stabilization is smaller for radicals with a boronic ester substituent relative to the corresponding borinic ester or borane (Figure A) . This stabilization is the first key feature for designing an iodine‐atom‐transfer process according to the pioneering work of Kharasch, Curran, and co‐workers .…”
Section: Figurementioning
confidence: 99%
“…[16] Then ature of the alkyl chain at boron can be easily modified with ahigh level of stereocontrol through homologation reactions upon treatment with carbenoid-type reagents. [33,34] This stabilization is the first key feature for designing an iodine-atom-transfer process according to the pioneering work of Kharasch, Curran, and co-workers. [33,34] This stabilization is the first key feature for designing an iodine-atom-transfer process according to the pioneering work of Kharasch, Curran, and co-workers.…”
mentioning
confidence: 99%
“…[17][18][19] Our long-standing interest in developing mild methods for the functionalization of alkenes through radical pathways [20][21][22][23][24][25][26][27][28][29][30][31][32] inspired us to investigate iodoalkylation involving 1-borylated alkyl radicals to give g-iodoalkylboronates.B ased on EPR studies and calculations,W alton, Carboni, and co-workers reported that 1-borylated radicals are stabilized when the boron is sp 2 -hybridized, however the extent of stabilization is smaller for radicals with aboronic ester substituent relative to the corresponding borinic ester or borane ( Figure 1A). [33,34] This stabilization is the first key feature for designing an iodine-atom-transfer process according to the pioneering work of Kharasch, Curran, and co-workers. [35][36][37][38][39][40][41] Matching the philicities of the radicals and alkenes involved in the process is the second key feature for the success of the reaction.…”
mentioning
confidence: 99%